Socialization of Implementation of Automatic Identification System (AIS) Technology on Passenger and Fishing Boats to Enhance Maritime Safety and Security on Lae-Lae Island - ., Rahimuddin; Renreng, Ilyas; Baso, Suandar; Putra, Erwin Eka; Arma, Lukmanul Hakim; ., Hamzah (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
The density of ships in the Makassar harbor shipping channel increases along with the increase in the number of ships entering and leaving the port and ships passing through the shipping channel, including traditional passenger ships and fishermen from the surrounding islands. This situation can increase the risk of a ship collision. Traditional passengers and fishing boats have the potential to collide because their boats are not detected by other ships. This situation can occur because they do not have a device that can exchange ship position information, namely, the Automatic Identification System (AIS). The use of an AIS is an alternative solution that can be detected by large ships and provides ship navigation actions to avoid collisions. The socialization of AIS technology and its application to the operators, owners of traditional passenger ships and fishermen is the first step in introducing AIS technology for sailing safety. The activity, which consisted of lectures and Q&A sessions, was used in partnership with the local administration and was attended by 15 people. The activity was assessed by asking the same six questions before and following the presentation. Five participants (33%) were selected for assessment. The initial evaluation revealed that none (0% of participants) were familiar with AIS devices that could supplement radar function. In the final review, 83% of the accumulated responses were correct, up from 25% previously; 17% did not comprehend how AIS works. This activity improves participants' grasp of the importance of utilizing AIS, how it works, and the necessity for sample devices to aid further comprehension.